Formação em serviço e saberes docentes: uma análise desse processo em um curso de mídias em educação - Françoso, Ana Cláudia Giglioti (Universidade Federal de São Carlos, 2023)
This study aims to analyze the potential of a distance learning specialization course, entitled Media in Education, exploring the knowledge resulting from this process for the training and professional performance of participating teachers. This objective was proposed based on the following research question: what is the knowledge provided by a distance learning specialization course in the in-service training of basic education teachers, focusing on the mastery of new technologies to be used in pedagogical practice? For the development of the study a qualitative research of exploratory-descriptive nature (SELLTIZ et al, 1965) was carried out, divided into three moments: 1) bibliographic review of the theme; 2) theoretical review and 3) production and analysis of empirical data, generated by applying an online questionnaire to former teachers of the course, for which we obtained 29 participants, and a semi-structured interview with one of the coordinators of the specialization. The data were analyzed based on the theoretical conceptions about knowledge and continuing education in service. The analysis allowed us to identify that a course offered in EaD modality, with the flexibility to manage the studies, in an inter-relationship between professional peers and the possibility of applying theory in one's own practice, can incisively contribute in a significant way to the teacher's training, security and autonomy in considering the Digital Information and Communication Technologies (TDICs in Portuguese) as valuable tools, allies of their teaching practice. Therefore, our defense, in this study, is for a continued in-service training, which is a university professional training (NÓVOA, 2017, 2019), which contemplates the exercise of the profession according to its real demands and that allows the teacher to evaluate the potential need and the quality of educational innovation that should be constantly introduced in institutions, aiming at the construction of a collective professional culture (IMBERNÓN, 2011), taking as reference their knowledge (GAUTHIER, 1988; TARDIF, 2014). This research also aims to advance studies in the area of Continuing Education in Service of Teachers, through the verification of relevant aspects to the participants of the specialization program in EaD, identifying the contributions of this training for the practices of current teachers and enhancing the importance of actions of this nature. As a product, we intend to produce an e-book that includes the main research developed by our study group, especially in relation to the theme addressed in this dissertation on In-service Training.
In-service training and teaching knowledge: an analysis of this process in a course on media in education
Keywords: Formação continuada em serviço; Especialização EaD; Mídias em educação; TDICs; Saberes docentes; Continuing in-service training; EaD specialization; media in education; TIDICs in portuguese; Teacher knowledge; CIENCIAS HUMANAS::EDUCACAO